EFFECT OF SOWING TECHNIQUES AND WEED CONTROL METHODS ON WEED GROWTH PERFORMANCE OF WHEAT (TRITICUM AESTIVUM L.) - PANDEY, D.K.; GANGWAR, K.S.; SHARMA, S.K. (Annals of Agricultural Research, 2014)
A field experiment was conducting was conducted during 2003 to 2004 at the Project Directorate for Cropping Systems Research, Modipuram, Meerut, to find out the most effective weed control method in controlling weed in wheat. Result indicated that stale seedbed resulted in higher wheat yield (4.45t/ha) as compared to conventional tillage (4.22 t/ha), among weed control treatments, herbicides + one hand weeding (5.34 t/ha) and criss-cross sowing + herbicides + one hand weeding (5.66 t/ha) recorded at par yield but significantly superior to two hand weeding (4.78 t/ha). The highest net return (Rs. 35,505/ha) was recorded under criss-cross sowing + herbicides + one hand weeding and proved to be superior over other methods of weed control.